49th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2011
DOI: 10.2514/6.2011-936
|View full text |Cite
|
Sign up to set email alerts
|

FUN3D and CFL3D Computations for the First High Lift Prediction Workshop

Abstract: Two Reynolds-averaged Navier-Stokes codes were used to compute flow over the NASA Trapezoidal Wing at high lift conditions for the 1 st AIAA CFD High Lift Prediction Workshop, held in Chicago in June 2010. The unstructured-grid code FUN3D and the structured-grid code CFL3D were applied to several different grid systems. The effects of code, grid system, turbulence model, viscous term treatment, and brackets were studied. The SST model on this configuration predicted lower lift than the Spalart-Allmaras model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…The term "FT" in the table indicates fully turbulent, and the term "trans set" indicates that transition locations were fixed a priori, as described in Section II. Note that some of the listed computations were actually a part of the earlier study by Park et al, 12 but they are included here for comparison purposes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The term "FT" in the table indicates fully turbulent, and the term "trans set" indicates that transition locations were fixed a priori, as described in Section II. Note that some of the listed computations were actually a part of the earlier study by Park et al, 12 but they are included here for comparison purposes.…”
Section: Resultsmentioning
confidence: 99%
“…All computations were performed on "medium" grid levels from the workshop grid refinement study. Grid study results for the UH6 and SX1 grids can be found in Park et al 12 The grids denoted as UH6 (without brackets) and UH16 (both with and without brackets) were unstructured mixed-element grids. SX1 (without brackets) was a structured multi-zone grid, and UX9 was the same grid written in unstructured format (hexahedra).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This code provides discretely consistent adjoint capabilities for sensitivity analysis. For many years, FUN3D has been used to perform adjoint-based mesh adaptation 9,10,11,12 and design optimization, 13,14 including optimization of the near-field sonic-boom waveforms, which represent the current state of the art in sonic boom mitigation. In the present paper, we are looking beyond the current state-of-the-art approaches to directly optimize ground-based sonic boom metrics rather than continue working on near-field target matching.…”
Section: Introductionmentioning
confidence: 99%